Pengaruh Customer Relationship Management Terhadap Loyalitas Jamaah Umroh pada PT Cahaya Berkah Safar: Al-Ghazi Tour & Travel - Yusnita Effendy, Mutya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Umrah industry in Indonesia is experiencing rapid growth due to the increasing demand for Hajj and Umrah services from the Muslim community in Indonesia. Tight competition in the Umrah travel services industry in Indonesia motivates business actors to continue to innovate in an effort to attract and retain Umrah pilgrims. One of the strategies used is the implementation of Customer Relationship Management practices. This research aims to identify and analyze the impact and relationship between Customer Relationship Management and Umrah Pilgrim Loyalty on users of Umrah travel services at PT Cahaya Berkah Safar (Al-Ghazi Travel & Tour). This research uses quantitative methodology with descriptive statistical analysis. The research sample was obtained through purposive sampling, namely selecting participants based on certain characteristics that were considered relevant to the research. The findings show that Customer Relationship Management has a significant impact, accounting for 78.9% of the overall impact observed.